Correlation Between Rift Valley Fever Virus (RVFV) Neutralizing Antibody Titers in Vaccinated Sheep and Effective Dose 50 (ED50) in Vaccinated Mice - Khafagi, Heba A; Aziz, Heba MG Abdel; AM, Amal; WM, Barghooth; Sharfik, Narmeen G (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Rift valley fever is an arthropod-born, multispecies zoonotic viral disease. Control of RVF disease depends mainly on vector control andvaccination of susceptible animals. The present work aims to detect the correlation between Rift Valley Fever Virus (RVFV) neutralizingantibody titers in vaccinated sheep using Serum Neutralization test as in vitro test and effective dose fifty in vaccinated mice as in vivopotency test and determine if they can be alternative to each other. In this work,17 inactivated RVFV vaccine batches were evaluated,applying SNT for serum samples of vaccinated sheep and ED50 in vaccinated mice. The two models of tests showed compatible results,where the same 14 vaccine batches showed satisfactory results [(SNT >1.5) and (ED50
Keywords: : Effective Dose Fifty; Inactivated Rift Valley Fever vaccine; Mice; Serum Neutralization Test,; Rift Valley Fever, Sheep